Effect of Amine Volatility on Aerosol Droplet Development in Absorption Columns. (July 2017) - Majeed, Hammad; Knuutila, Hanna; Hillestad, Magne; Svendsen, Hallvard F.
Abstract: In absorption processes aerosols are generated by spontaneous condensation or desublimation processes in supersaturated gas phases. Amine volatility is a vital screening parameter for amines to be used in CO2 capture. Higher volatility will result in higher losses through the gas phase and may also result in undesired aerosol formation and thereby to higher amine emissions and environmental impact. These amine emissions are one of the challenges in the realization of full scale absorption based post combustion CO2 capture plants. It is crucial to understand the mechanisms governing in particular the aerosol formation and development through a column as this is not well understood. Rigorous modelling of aerosol dynamics leads to a system of partial differential equations. In order to understand mechanics of a particle entering an absorber an implementation of a droplet model is created in Matlab. The model predicts the droplet size, the droplet internal variable profiles and the mass transfer fluxes as function of position in the absorber. The focus of this paper is to study the effect of amine volatility and how this influences the droplet composition, growth rate, final size and the resulting amine loss.